DAMPAK KONVERSI HUTAN MENJADI LAHAN PERTANIAN TERHHADAP PEMBANGUNAN DESA STUDI KASUS DI HUTAN LINDUNG PINANG LUAR – KABUPATEN KUBU RAYA - Handayani Handayani; Abdul Hamid A. Yusra; Wanti Fitrianti (Fakultas Pertanian Universitas Tanjungpura, 2022)
Forest conversion activities into non forestry purposes impacts on decreasing of forestfunction as a main role sustainable development, especially as water regulators and as carbon storage. Therefore, deforestation not only causes a direct loss of forest habitat but also leads to indirect impacts as ecosystem services deteriorate or fail. Forests provide ecosystem services that include the regulation of weather and climate at local, regional and even global levels. Existence of protected forest Pinang Luar ± 3.228 acres take an important part and people living in the area has a high dependency on the forest. Farming activities become a treat to the forest and their indications show that cropland and palm estate already in the forest area. Land cover changes in protected forest Pinang luar at 2003 – 2012 impacts on villages at ring 1 area hierarchy decrease cause by population growth are not followed by the additional of infrastructures in economy, health and education. It is also caused by landconversion that occurred in the protected forest Pinang Luar. In the period 2003 - 2012, the villages directly affected (ring 1) have a level area hierarchy is much worse compared to villages that are not directly affected (Ring 2). And it affected to the development of the villages in the ring 2 which is better than the village at ring 1. These conditions happen because at the village in ring 1 change only on land not on the impact on the level of development that could affect the region hierarchy. This is in contrast with the ring 2 villages where the changes occur not only on land but also on its impact on the development so as to enhance the region hierarchy in ring 2 villages.